4-(5,6-Dihydrobenzimidazo[1,2-c]quinazolin-6-yl)benzene-1,3-diol dimethyl sulfoxide monosolvate - Naser Eltaher Eltayeb; Siang Guan Teoh; Chin Sing Yeap; Hoong-Kun Fun (Acta Crystallographica Section E, 2011)
In the title solvated benzimidazole compound, C20H15N3O2·C2H6OS, both the benzimidazole fused-ring system and the complete dimethyl sulfoxide solvent molecule are disordered over two sets of sites, in 0.750 (5):0.250 (5) and 0.882 (4):0.118 (4) ratios, respectively. The conformation of the pyrimidine ring is close to a half-chair for the major disorder component, whereas for the minor component it is close to a boat. The dihydroxyphenyl ring is almost perpendicular to the mean plane of the benzimidazole ring [dihedral angle = 87.3 (2)° for the major disorder component and 88.3 (5)° for the minor disorder component]. In the crystal, molecules are linked into layers parallel to (110) by O—H...N and C—H...O hydrogen bonds. A bifurcated O—H...(O,S) bond links the benzimidazole and solvent molecules.